Marketing Strategy Through Digital Marketing To Increase Sales Volume (Case study on the ECO laundry business at JL.Danau Panorama, Bengkulu City) - Liza Febriani; Eti Arini (Penerbit ADM, 2023)
This study aims to determine marketing strategies through digital marketing in order to increase sales volume (a case study in the eco laundry business at Jl.Danau Panorama, Bengkulu City. by consumers. Prices are set in accordance with the capital issued by the Laundry Eco business. The location where the Eco Laundry business was founded is very strategic. Promotion of the Eco Laundry business in carrying out its promotional activities has utilized developing technology, namely social media. The existence of digital marketing makes it easy to get information. From this research it can be concluded that the strengths are affordable prices, satisfactory quality of laundry results.Weaknesses are higher machine production costs.Opportunities faced by Laundry Eco, which has utilized internet technology by marketing through social media.The threat faced is rising raw material prices. Digital marketing is used by Laundry Eco, namely social media Facebook, Instagram and WhatsApp.